Cilioretinal Artery Occlusion Combined with Central Retinal Vein Occlusion: What Is the Best Imaging Modality for the Follow-Up? - Mahmut Kaya; Taylan Ozturk; Ziya Ayhan; Nilufer Kocak; Suleyman Kaynak (Case Reports in Ophthalmological Medicine)
We report retinal structural changes of a 37-year-old man diagnosed with the concomitant occlusion of cilioretinal artery and central retinal vein. Comprehensive ophthalmological evaluation was performed, followed by spectral-domain optical coherence tomography (SD-OCT, Heidelberg), optical coherence tomography angiography (OCT angiography, Optovue Inc., Fremont, California, USA), fluorescein angiography, and color fundus photography. The use of OCT angiography and en face SD-OCT imaging as an adjunct test to map out correlative paracentral scotomas during follow-up allowed us to evaluate cilioretinal artery occlusion in the best way due to obtaining satisfactory images of the normal retinal vascular networks and areas of nonperfusion and congestion at various retinal levels.